Development and characterization of biomass lignin and plant protein-based adhesives - Pradyawong, Sarocha (Kansas State University, 2018)
The depletion of petroleum feedstock along with significant concerns about health and environment lead to an interest in alternative green products. Soy protein (SP) adhesives have great potential as a renewable material for wood industries. The obstacle of applying SP-based adhesives is its relatively low water resistance. The overall objective was to enhance the water resistance of SP adhesives through protein and lignin interaction. An improvement of adhesion performance, flowability, and thermal properties of SP adhesives was achieved through the protein and lignin interaction and formation of protein and lignin copolymer. pH adjustment is a simple process to change protein folding and lignin properties. Cleavage of β-O-4 linkage was observed at pH 8.5 and pH 12, resulting in an increase in lignin active groups and the changes in lignin particle size and thermal properties. Cross-linking of protein with lignin took place via carbonyl, amino, and hydroxyl groups. Multiple-point and non-specific interactions between lignin and protein resulted in stronger lignin-protein networks and changes in properties, which improved wet adhesion strength of protein adhesives. In addition, lignin was depolymerized by laccase enzyme with the presence of mediator, TEMPO, to induce a formation of the strong lignin-protein network. The formation of the strong lignin-protein network increased the wet adhesion strength by 106% and the partial wood failure was observed after the three-layer wood test. A better performance was also observed on the three-cycle soaking test. The adhesion performance of SP adhesives was also greatly affected by lignin particle size and the protein to lignin ratio at pH 4.5. The wet adhesion strength of SP adhesives increased as lignin particle size decreased. The protein-lignin adhesive with protein to lignin ratio of 10:2 (w/w) at 12% solid content had the lowest contact angle and the highest wet adhesion strength of 4.66 MPa, which is 53.3% higher than that of 10% pure SP adhesive. Lignin-protein interactions, water resistance property, and glue line pattern had strong influences on an adhesion performance. Lignin and soy protein were modified at pH 4.5, 8.5 and 12. The maximum increase (620%) in water resistance was found at pH 12 with an addition of lignin. After the protein was unfolded (pH 8.5) and denatured (pH 12), it was refolded by shifting pH to 4.5. The better-wet adhesion performance was obtained at pH 4.5, 8.5-4.5 and 12 with rigid glue line. Shifting pH from 8.5 to 4.5 promoted lignin-protein interaction and increased adhesion performance. The protein-lignin adhesives using absolutely renewable materials and practical processes showed an excellent potential to replace the petroleum-based adhesives and fulfill the global demand for green products and technologies.
Keywords: Biomass lignin; Protein; Cross-linking interactions; Adhesive; Mechanical property; Thermal property